2010
DOI: 10.2147/vhrm.s7343
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cardiovascular risk factors to prevent cognitive decline and dementia: a systematic review

Abstract: Background:Over the last decade, evidence has accumulated that vascular risk factors increase the risk of Alzheimer disease (AD). So far, few randomized controlled trials have focused on lowering the vascular risk profile to prevent or postpone cognitive decline or dementia.Objective:To systematically perform a review of randomized controlled trials (RCTs) evaluating drug treatment effects for cardiovascular risk factors on the incidence of dementia or cognitive decline.Selection criteria:RCTs studying the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 58 publications
1
64
0
1
Order By: Relevance
“…Additionally, ACE activity in the CSF was positively correlated with both plasma and CSF levels of 27-OH (45). Accumulating data support an association between hypertension with cognitive function and dementia (46), although insufficient evidence showed that antihypertensive drugs can really prevent cognitive decline or dementia (47). Animal studies have shown that ACE inhibitors enhance cognitive performance (48), and improve learning and retention of memory (49).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ACE activity in the CSF was positively correlated with both plasma and CSF levels of 27-OH (45). Accumulating data support an association between hypertension with cognitive function and dementia (46), although insufficient evidence showed that antihypertensive drugs can really prevent cognitive decline or dementia (47). Animal studies have shown that ACE inhibitors enhance cognitive performance (48), and improve learning and retention of memory (49).…”
Section: Discussionmentioning
confidence: 99%
“…31 As yet, there is no conclusive evidence that antiplatelet or cholesterol-lowering drugs have a positive effect on dementia disorders or their progression. 32 But cognitive impairment was not defined as the primary endpoint of these studies. Older people benefit from medical secondary prevention even without an existing CHD.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Total plasma homocysteine (Hcy) and cardiovascular risk factors have been suggested as potential risk factors for small vessel disease in vascular dementia and AD [10,11,12,13,14,15,16]. Studies so far have given equivocal results [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%